Challenges in Developing Data Collection Systems in a Rapidly Evolving Higher Education Environment. Issue 157 (17th May 2013) - Borden, Victor M. H.; Calderon, Angel; Fourie, Neels; Lepori, Benedetto; Bonaccorsi, Andrea
Abstract: Efforts to develop common higher education data standards are expanding both within and across countries. The institutional research (IR) community plays a critical role in assuring that these efforts capture the diverse manifestations of the postsecondary and tertiary education systems and promote responsible comparisons.